2002
DOI: 10.1128/jcm.40.11.4114-4120.2002
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Human Astrovirus in Central Australia (1995 to 1998) and Comparison of Deduced Serotypes Detected from 1981 to 1998

Abstract: The incidence of astrovirus infection was determined among infants and young children admitted to Alice Springs Hospital (central Australia) with gastroenteritis from 1995 to 1998. Astrovirus was detected by reverse transcription-PCR in 33 of 495 stool samples, and this represented 4.3% of a total of 774 stool samples tested for astrovirus, rotavirus, and Norwalk-like viruses. Astrovirus incidence was substantially lower than that of rotavirus but higher than that of Norwalk-like viruses both overall and in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 20 publications
5
23
1
2
Order By: Relevance
“…Studies have shown that astroviruses occur preferentially during the colder months of the year (Phan et al 2004, Galdiero et al 2005) even though other investigations have shown a higher viral incidence during warmest months (Guerrero et al 1998, Naficy et al 2000. Other studies report a year-round occurrence of astroviurs infection (Schnagl et al 2002, Giordano et al 2004. In this study, the infection by astrovirus occurred mainly from September to March, considered the rainy season in the region.…”
Section: Discussionmentioning
confidence: 60%
“…Studies have shown that astroviruses occur preferentially during the colder months of the year (Phan et al 2004, Galdiero et al 2005) even though other investigations have shown a higher viral incidence during warmest months (Guerrero et al 1998, Naficy et al 2000. Other studies report a year-round occurrence of astroviurs infection (Schnagl et al 2002, Giordano et al 2004. In this study, the infection by astrovirus occurred mainly from September to March, considered the rainy season in the region.…”
Section: Discussionmentioning
confidence: 60%
“…Astroviruses have been increasingly identified as important agents of acute gastroenteritis in children (7,14,23,31,32) and the elderly (11). Outbreaks of astrovirus gastroenteritis have been reported for young adults, including military recruits (2), students, teachers (28), and children (25).…”
Section: An Outbreak Of Astrovirus Gastroenteritis Occurred In the Prmentioning
confidence: 99%
“…HAstVs were detected throughout the year. Two co-infections with G2P [4] rotavirus were confi rmed by RT-PCR. No co-infection with norovirus was found ( Table).…”
Section: The Studymentioning
confidence: 99%
“…Today, astroviruses, along with rotaviruses and caliciviruses, are considered important viral agents of acute pediatric gastroenteritis (2). These viruses have been associated with endemic diarrheal episodes and outbreaks of gastroenteritis in industrialized (4,5) and nonindustrialized countries (6,7). Although Madagascar is a society of considerable diversity, no studies have yet been reported on the prevalence and molecular epidemiology of HAstV among children with acute gastroenteritis in the country.…”
mentioning
confidence: 99%